(untitled) (London, 1998)
This second edition focuses upon EMAS and ISO 14001, while the auditing approach within the ISO 14000 series is also examined. The examination of strategy now places more emphasis on cost reduction and differentiation as a means to achieving a competitive advantage through environmental management, while many areas, such as that on life cycle assessment, have been updated.
Quản lí môi trường và công nghệ sạch
Keywords: Industrial management,Quản trị công nghiệp; Environmental aspects,Diện mạo môi trường